E-Learning Pricing Model Policy for Higher Education - Reina Setiawan; Fransiskus Asisi Suseno Arif; Jodi Oktrianto Putro; Elfindah Princes; Fitriani Tupa R. Silalahi; Ira Geraldina; Eka Julianti; Julia Safitri (IEEE Access, 2023)
The technological advancement in learning has made it possible for students to study beyond space and time restrictions, known as online learning. Impacted by the pandemic for an extended period, most students have adapted to online learning and, even more, have realized the vast benefits of online learning despite all the minor disadvantages. As a result, worldwide institutions, including Indonesia, are now offering online degrees and courses. Previous studies have shown contradictory results of cost factor effects on online courses, from the least important to the most critical factor for student achievements. Therefore, deciding the online course rates has been a major concern for online course providers. This research aims to answer the fundamental question of designing costs for online learning by analyzing online course preferences and ensuring sustainability by proposing a framework for the E-learning Pricing Model Policy in Higher Education using literature studies and qualitative approaches. The results show four main phases: the preparation phase, which conducts market research to understand consumer demand and behavior; the implementation phase, which includes marketing expenses and tutor fees; evaluation phase, which includes the course content material and video production revisions for further implementation. In addition, the infrastructure phase as the Learning Management System’s virtual space is added with the Cloud Expenses. However, as a limitation of this research, countless factors influence online course rates, and no exact number can determine those rates. Nevertheless, the course cost can be estimated by considering the factors that affect the overall cost and the number of learners who take the course. As a result, this framework acts as an essential foundation for institutions to determine sustainable online course rates.